Iatrogenic orbital cerebrospinal fluid leak in a young pediatric patient: Factors to consider. (January 2021) - Niermeyer, Weston L.; Allen, David Z.; Kern, Charlemagne; Elmaraghy, Charles
Abstract: Orbital abscess and subperiosteal abscess are pathologies which may require surgical treatment in the pediatric patient. Though rare, orbital cerebrospinal fluid (CSF) leak is a serious complication of abscess drainage. This paper presents a unique 5-month-old male with transorbital abscess drainage complicated by CSF leak. An endoscope was used to repair the defect through the orbitotomy incision. There was no evidence of persistent leak at follow-up. The surgical approach likely contributed to the complication, and the otolaryngologist played a key role in the leak repair. This case should serve to raise the awareness regarding considerations to avoid orbital CSF leak.